FEASIBILITY ANALYSIS OF PATCHOULI BUSINESS IN LERE VILLAGE BASALA DISTRICT KONAWE SELATAN REGENCY - Saenal Wahid (Institute of Computer Science (IOCS), 2022)
This study aims to determine the income and feasibility of patchouli agroindustry in Lere Village, Basala District, South Konawe Regency. The sampling technique in this study used the census method and the informants in this study were patchouli farmers in Lere Village, Basala District, South Konawe Regency as many as 16 respondents. The results showed that the results of the feasibility analysis of patchouli agroindustry were feasible to run with the total business income generated, which was Rp. 109,809,734., with the average income of each patchouli farmer is Rp. 6,863,108., and based on the results of the calculation of the R/C Ratio, which is 3.58 > 1 and is said to be feasible, which means that each expenditure is Rp. 100 will provide an income of Rp. 358. Based on the results of the calculation of the BEP, the price is Rp. 131,081., and BEP production of 90 Kg. Meanwhile, the production value of patchouli agroindustry is 324 Kg with a selling price of Rp. 470,000 greater than the price BEP and production BEP, then the patchouli agroindustry is said to be profitable.